Method for treating chlorohydrocarbon-polluted underground water by utilizing biochar in cooperation with zero-valent iron
The biochar-ZVI material prepared through the 700-900℃ pyrolysis process uses synergistic chemical action to improve the treatment efficiency of chlorinated hydrocarbons contaminated groundwater, solves the problems of surface passivation and fast reaction rates of zero-valent iron materials, and achieves efficient and stable groundwater repair.
Patent Information
- Application Number
- CN202411852436.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the prior art, when treating chlorinated hydrocarbons contaminated groundwater, the surface passivation and reaction rates of zero-valent iron materials are too fast, resulting in inactivation, and it is difficult to maintain the repair effect and control pollution for a long time.
Biochar synergistic zero-valent iron materials are prepared by 700-900℃ pyrolysis process. Through the synergistic chemical action between biochar and ZVI, the electron capacity and reactivity of zero-valent iron are improved, the surface passivation problem is solved, and effective reactions are maintained in an alkaline environment.
It significantly improves the treatment efficiency of chlorinated hydrocarbons, enhances the sustained release and stability of zero-valent iron, reduces the cost of groundwater repair, adapts to a wide range of scales, and adapts to complex groundwater environmental conditions.
Smart Images

Figure CN119528316A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of groundwater remediation, and more specifically, relates to a method for treating groundwater contaminated by chlorinated hydrocarbons by utilizing biochar in collaboration with zero-valent iron. Background Art
[0002] Chlorinated hydrocarbon compounds (such as common trichloroethylene, chloroform, carbon tetrachloride, etc.) are widely used. For example, carbon tetrachloride was widely used as a dry cleaning agent and fire-fighting agent, while trichloroethylene is often used as a metal degreasing agent. However, these compounds are also recognized as environmental endocrine disruptors, posing potential risks to human health and ecosystems. The widespread use of chlorinated hydrocarbons in industrial production often causes them to enter the groundwater system as pollutants, and because they are difficult to degrade rapidly through natural processes, the pollution of groundwater systems is long-term. In addition, the poor solubility and relative density of chlorinated hydrocarbons greater than water make them easy to migrate vertically in groundwater, accumulate on impermeable layers, and then slowly release into the groundwater system. This slow-release characteristic exacerbates the persistent pollution of chlorinated hydrocarbons in the environment, posing major challenges and high treatment costs to the purification of groundwater.
[0003] Zero-valent iron has been widely used in the remediation of chlorinated hydrocarbons due to its high electron capacity and strong reducing property. Compared with other remediation technologies, zero-valent iron is particularly prominent in groundwater remediation due to its injectability. However, the long-term application feasibility of this method is limited by the possibility that its reaction surface may be deactivated due to oxidation or blockage. In order to solve this problem, researchers have developed a variety of improvement schemes. For example, Chinese patent application 202410614427.4 introduces a method for enhancing the reduction of chlorinated hydrocarbons by zero-valent iron using clay minerals and sulfidation treatment; Chinese patent application 201910329393.3 uses tannic acid to enhance the reactivity of zero-valent iron with chlorinated hydrocarbons; and Chinese patent application 202211111093.6 combines zero-valent iron with biochar (biochar and zero-valent iron only have physical effects, and biochar is used to improve the dispersibility of zero-valent iron), and performs phosphorylation treatment to introduce microstructural cracks, and uses the interaction between Fe and P elements to effectively prevent the surface passivation problem, thereby maintaining the effective transfer of electrons. These existing studies provide some help in improving the efficiency and durability of zero-valent iron in remediating chlorinated hydrocarbon-contaminated environments.
[0004] Zero-valent iron remediation technology faces some inherent contradictions when dealing with chlorinated hydrocarbon groundwater contamination. In order to overcome the decreased activity caused by surface passivation, technical improvements are usually aimed at accelerating the reaction rate of zero-valent iron. However, although this accelerated reaction has its advantages, it also causes a series of problems, which reduces the persistence or slow release of zero-valent iron during the migration of chlorinated hydrocarbons in groundwater, resulting in the need for repeated injection at multiple points, which greatly increases the engineering complexity of the project. In addition, although the reaction efficiency of zero-valent iron has been improved by various methods, this enhanced reactivity also means that its persistence in groundwater, especially in the redox alternation zone, is reduced, making zero-valent iron more susceptible to oxidation by coexisting oxidizing substances, thereby weakening the remediation efficiency. For example, after sulfidation treatment, the reduction ability of zero-valent iron is enhanced, but it is more likely to react with oxidizing substances in the environment, limiting its application in a wide area. Furthermore, current technology shows poor results in treating residual non-aqueous phase liquids in complex sites or chlorinated hydrocarbon contamination in low permeability areas, making it difficult to maintain the remediation effect for a long time and effectively control the pollution.
[0005] Therefore, there is an urgent need for a technology that can both ensure the remediation efficiency and improve the sustained release of zero-valent iron. In terms of sustained release, Chinese patent application 202210241095.0 describes a method for preparing by mixing zero-valent iron powder, biochar, biocarbon source, emulsifier, stabilizer and water, which aims to distinguish the long-term, medium-term and short-term remediation capabilities of zero-valent iron. Chinese patent application 202210087096.4 introduces a moldable sustained-release agent for in-situ remediation of chlorinated hydrocarbon pollutants and a preparation method thereof, which involves a combination of emulsifier, recyclable oil, micron iron powder, industrial syrup, thickener, stabilizer, disintegrant and water. This combination effectively creates an environment in which zero-valent iron releases electrons slowly and enhances the sustained release of zero-valent iron, but the use of thickeners and stabilizers may hinder the effective transfer of electrons and reduce the remediation efficiency. The purpose of using such materials is to improve the remediation effect, reduce the construction frequency, and minimize environmental interference. Nevertheless, these materials still face some defects in the remediation of chlorinated hydrocarbon groundwater, such as the complicated preparation process and the need to design specific embedding composite materials according to different groundwater environments. For example, Chinese patent application 202210087096.4 designs specific materials for the living conditions of anaerobic organisms. These technical challenges may lead to reduced contact efficiency with pollutants in practical applications. Summary of the invention
[0006] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for treating groundwater contaminated by chlorinated hydrocarbons by using biochar in collaboration with zero-valent iron. The biochar-cooperative zero-valent iron material is prepared by a specific process of pyrolysis at 700-900°C, which can achieve effective treatment of chlorinated hydrocarbons in groundwater containing chlorinated hydrocarbons. The preparation process of the biochar-cooperative zero-valent iron material in the method of the present invention is simple, which can break through the traditional physical slow-release restrictions. The synergistic chemical effect between biochar and ZVI is used to significantly increase the electron capacity of zero-valent iron in the reaction and improve the reaction activity, effectively solving the problem that the divalent iron produced by zero-valent iron after oxidation cannot react effectively, thereby enhancing the storage and utilization efficiency of electrons. In addition, the method of the present invention greatly reduces the cost of groundwater remediation, and can adapt to a wide range of scales, effectively coping with various chlorinated hydrocarbon pollution scenarios. The present invention not only improves the remediation efficiency, but also optimizes the economic efficiency, and provides a more effective and sustainable technical solution for the remediation of groundwater contaminated by chlorinated hydrocarbons.
[0007] To achieve the above object, according to the present invention, a method for treating groundwater contaminated by chlorinated hydrocarbons using biochar in combination with zero-valent iron is provided, characterized in that the method comprises the following steps:
[0008] (1) mixing biomass with iron-containing materials and pyrolyzing them at 700-900° C. under oxygen-limited conditions to obtain a biochar-ZVI material;
[0009] (2) The biochar-ZVI material is injected into the groundwater containing chlorinated hydrocarbons to be treated for a reaction for at least 7 days, thereby achieving the treatment of chlorinated hydrocarbons in the groundwater containing chlorinated hydrocarbons; wherein the pH value of the groundwater containing chlorinated hydrocarbons does not exceed 11.
[0010] As a further preferred embodiment of the present invention, step (1) specifically includes the following sub-steps:
[0011] (1-1) preparing dried biomass with a particle size of ≤0.5 mm, and pyrolyzing the biomass at a temperature of 300° C. to 460° C. for 30 min to 2 h under oxygen-limited conditions to obtain precursor charcoal;
[0012] (1-2) The precursor carbon and the iron-containing material are weighed and mixed in a mass ratio of (0.1-0.5):1, and then water is added to soak and stir and then allowed to stand; then the solid-liquid separation is performed, and the obtained solid is dried and pyrolyzed at a temperature of 700-900° C. under oxygen-limited conditions for 1-3 hours to obtain a biochar-ZVI material.
[0013] As a further preference of the present invention, in step (1-2), the amount of water added satisfies a water-to-solid mass ratio of (10-25):1.
[0014] The stirring time is more than 2 hours, and the standing time is more than 12 hours.
[0015] As a further preferred embodiment of the present invention, in step (2), the biochar-ZVI material is added to the groundwater containing chlorinated hydrocarbons to be treated at a concentration of 0.05-1.0 g / L.
[0016] As a further preferred embodiment of the present invention, in step (2), the concentration of chlorinated hydrocarbons in the groundwater containing chlorinated hydrocarbons to be treated is between 20 and 1000 ppm.
[0017] As a further preferred embodiment of the present invention, in step (1), the biomass is wood waste, preferably at least one of bamboo and coconut shell.
[0018] As a further preferred embodiment of the present invention, in step (1), the mass ratio of the biomass dry basis to the iron-containing material is (0.3-2.0):1.
[0019] The iron-containing material is at least one of ferrous sulfate, ferric sulfate, ferrous chloride, ferric chloride, ferric oxide, zero-valent iron, and ferrosoferric oxide.
[0020] Through the above technical scheme conceived by the present invention, compared with the prior art, the present invention utilizes the specific process of pyrolysis at 700-900°C to prepare biochar-cooperative zero-valent iron materials. Since no passivation is performed and no additional activator is required, the problem of surface passivation and deactivation caused by too fast reaction rate of zero-valent iron materials in the prior art can be effectively solved. In order to avoid surface passivation of zero-valent iron materials in the prior art, sulfurization modification is usually performed, which significantly reduces the migration performance of the material, and the remediation range for in-situ groundwater remediation is relatively small. The biochar-zero-valent iron (ZVI) material in the present invention not only utilizes the dispersibility of biochar, but also the biochar prepared under specific temperature conditions enhances the material's treatment efficiency for chlorinated hydrocarbons and the stability of the material. Different from the combination of biochar and zero-valent iron described in patents 202210241095.0, 202311551167.2 and 201710646025.2, the biochar-ZVI material of the present invention disperses ZVI evenly on the surface of biochar during the preparation process, which solves the problem of self-aggregation in water and enhances the stability and reactivity of the material. More importantly, the present invention utilizes the divalent iron (Fe(II)) generated by biochar-ZVI during the reduction of chlorinated hydrocarbons. Due to the presence of biochar, compared with Fe(II) existing alone (e.g., Fe existing alone), the 2+ or Fe(OH)2) shows stronger reducing ability. 2+Or Fe(OH)2 cannot effectively reduce chlorinated hydrocarbons. This intermediate biochar-Fe(II) composite material can effectively reduce chlorinated hydrocarbons, significantly enhancing the ability of ZVI's oxidation product Fe(II) in degrading chlorinated hydrocarbon compounds, thereby improving the treatment efficiency and remediation effect.
[0021] The following is the detailed chemical reaction process:
[0022] Biochar-Fe 0 + RCl + H + → Biochar-Fe(II) + RH + Cl - (1)
[0023] 2 Biochar-Fe(II) + RCl + H + → 2 Biochar-Fe(III) + RH + Cl - (2)
[0024] The present invention uses a biochar-ZVI material prepared under specific conditions. In this material, the biochar can not only promote the uniform distribution of ZVI, but also react with Fe(III) formed after reducing chlorinated hydrocarbons (Formula (2)), thereby reducing Fe(III) to Fe(II) again. In addition, Fe(II) can further react with chlorinated hydrocarbons (Formula (1)), thereby significantly improving the treatment efficiency of chlorinated hydrocarbons. In the prior art, biochar prepared at low temperature is usually used to reduce Fe(III) (the low temperature temperature is 300°C to 500°C). This is because the oxygen-containing functional groups such as phenolic hydroxyl groups on the low-temperature biochar can provide the necessary electrons. However, the specific surface area of low-temperature biochar is relatively low (usually less than 10m 2 / g), which limits its performance in the early stage of the reaction, because ZVI is easy to agglomerate, which is not conducive to its effective dispersion, thus affecting its repair effect on chlorinated hydrocarbons. In contrast, the present invention uses biochar-ZVI prepared at a high temperature of 700-900°C, which has a larger specific surface area (~600m 2 / g) not only promotes the effective dispersion of ZVI in the early stage of the reaction, but also the biochar can react with the formed Fe(III) and reduce it to Fe(II), and participate in the reaction with chlorinated hydrocarbons again. Although the oxygen-containing functional group content of the high-temperature biochar of the present invention is low, its unique structure and high electron content make it possible to effectively promote the biochar-ZVI to reduce Fe(III) to Fe(II) and reduce chlorinated hydrocarbons in multiple ways, making maximum use of the potential electrons in the biochar, thereby improving the treatment efficiency of chlorinated hydrocarbons and the possibility of environmental remediation.
[0025] In the application of ZVI to treat chlorinated hydrocarbons, a key challenge is the increase in pH value in local areas of the water body during the reaction (refer to chemical reaction formulas (3) and (4)). This alkaline condition makes the sustained reaction of ZVI more difficult. In particular, when the oxidized Fe(II) is further converted into Fe(III), due to its strong adsorption, it easily forms a layer of coating on the surface of ZVI, thereby hindering the further chemical reaction of ZVI. Specifically, as the pH increases, the Fe(II) generated by the oxidation of ZVI is extremely sensitive to oxides and will be rapidly converted into Fe(III). Its strong adsorption will significantly hinder the reaction activity of ZVI (refer to chemical reaction formulas (3) to (6)). In the present invention, by introducing biochar prepared under specific high temperature conditions, the biochar has rich aromatic structures and a high specific surface area, which can effectively promote the reduction of Fe(III) to Fe(II). This process can still be carried out effectively in an alkaline environment, which can expand the remediation pH range for treating groundwater contaminated by chlorinated hydrocarbons and increase the remediation area of groundwater. This enables the present invention to adapt to more complex groundwater environmental conditions, enhances the applicability and effectiveness of restoration projects, and further improves the universal applicability and practical application value of environmental restoration technology.
[0026] Fe 0 + RCl + H2O → Fe 2+ + RH + Cl - + OH - (3)
[0027] 2Fe 0 + O2 + 2H2O → 2Fe 2+ + 4OH - (4)
[0028] Fe 2+ + Oxic → Fe 3+ (5)
[0029] Fe 3+ + 3OH - → Fe(OH)3 (6)
[0030] In the present invention, the combination of biochar and iron significantly enhances the reducing ability of biochar. Specifically, the originally stable carbon structure can stimulate potential reducing ability under the influence of iron, thereby promoting the release of electrons and optimizing the electron supply mechanism. Under normal circumstances, especially for biochar prepared at 700 to 900°C, its physical and chemical structure remains stable before and after the reaction and is difficult to oxidize. However, the biochar-iron composite material prepared in the present invention exhibits a synergistic effect that exceeds the sum of the effects of the individual components, further improving the treatment efficiency of chlorinated hydrocarbons.
[0031] In terms of the preparation of biochar-ZVI, the present invention is to obtain biochar-ZVI material by mixing biomass with iron-containing materials and then pyrolyzing them at a temperature of 700-900°C under oxygen-limited conditions. The present invention can preferably pyrolyze the biomass raw material at a temperature of 300°C to 460°C to obtain precursor carbon, which can further increase the specific surface area of the carbon material, so that the carbon material can load more iron when in contact with the iron-containing material, thereby enriching more iron elements in the biochar-ZVI material finally formed. At the same time, under the premise of introducing the precursor carbon preparation step, the processing temperature of the precursor carbon cannot exceed 460°C, so as not to release more reducing gases during the precursor carbon preparation process, but instead cause the subsequent precursor carbon to be mixed with the iron-containing material and in the oxygen-limited pyrolysis process at 700-900°C, it is impossible to produce enough reducing gases, and the iron-containing material cannot be reduced to ZVI, reducing the repair efficiency (of course, the biomass can also be directly mixed with the iron-containing material and directly subjected to oxygen-limited pyrolysis at 700-900°C). The biochar-ZVI composite material prepared by the present invention maintains high activity and stability, and provides an efficient and economical solution for the restoration of groundwater contaminated by chlorinated hydrocarbons.
[0032] In summary, compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The biochar-ZVI material used in the present invention has significant advantages in remediating groundwater contaminated by chlorinated hydrocarbons. The biochar-ZVI material prepared by the present invention using a specific process of pyrolysis at 700-900°C not only improves the reduction ability of biochar, but also enables Fe(II) and Fe(III) (the latter is reduced to Fe(II)) to effectively output electrons, thereby improving the reduction efficiency of chlorinated hydrocarbons. This method effectively converts the defects of the prior art into advantages, ensuring that the biochar-ZVI material can continuously and effectively treat chlorinated hydrocarbon pollution.
[0034] 2. The preparation process of the biochar-ZVI material in the present invention is simple and does not require the use of additional reducing agents or adhesives. Iron-based materials are widely available, and the gases generated during the pyrolysis process cause the iron-based materials to react with biomass to form biochar-ZVI with a stable structure and good reducibility. The present invention may preferably pyrolyze the biomass raw material at a temperature of 300°C to 460°C to obtain a precursor carbon, and then mix it with the iron-containing material and perform oxygen-limited pyrolysis at 700-900°C. This two-step preparation process can ensure that more iron-containing materials are loaded on the precursor carbon.
[0035] 3. The biochar-ZVI material in the present invention has a weak heterogeneous reactivity with oxygen, which means that the preservation cost during the preparation process is low and the loss cost during the transmission process in groundwater is low. Especially in groundwater environments with complex redox changes, this weak reactivity enables the material to better adapt to environmental conditions, greatly improving the remediation scope of chlorinated hydrocarbon-contaminated groundwater and enhancing the practicality and efficiency of environmental remediation projects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a comparison chart of the carbon tetrachloride treatment effects obtained by treating simulated chlorinated hydrocarbon contaminated groundwater in Example 2 by adding biochar, adding Fe(II), adding ZVI, adding Fe3O4 and adding biochar-ZVI respectively.
[0037] Figure 2 This is a comparison chart of the carbon tetrachloride treatment effects obtained by adding biochar-ZVI to treat simulated chlorinated hydrocarbon-contaminated groundwater with different pH values in Example 3 and Example 4.
[0038] Figure 3 This is the XPS graph of the Fe valence distribution on the solid after the reaction of biochar and Fe(III) in Example 9.
[0039] Figure 4 This is a comparison chart of the carbon tetrachloride treatment effects of biochar-ZVI prepared at different temperatures in Example 5 and Example 6 on simulated chlorinated hydrocarbon contaminated groundwater.
[0040] Figure 5 This is a diagram showing the carbon tetrachloride treatment effect obtained by synergistically treating simulated chlorinated hydrocarbon contaminated groundwater in Example 7 using biochar and Fe(II).
[0041] Figure 6 XRD characterization diagram of biochar-ZVI materials prepared at different temperatures in Example 1.
[0042] Figure 7 This is a diagram showing the carbon tetrachloride treatment effect of treating simulated chlorinated hydrocarbon contaminated groundwater after the ZVI and biochar-ZVI materials in Example 10 were oxidized in the water body for 1 day. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0044] Example 1: Preparation of biochar-ZVI material
[0045] The biochar-ZVI of the present invention is prepared by combining biomass with an iron-containing material.
[0046] In this embodiment, specifically:
[0047] First, bamboo from Longyan area of Fujian Province was selected as biomass, and the raw material (i.e., bamboo) was crushed to a particle size of ≤0.5 mm (particles of the target particle size can be obtained by sieving), washed, and dried at 80°C for 24 hours. Then, 100g of biomass (i.e., the dry basis mass of biomass is 100g) was weighed and subjected to oxygen-limited pyrolysis in a muffle furnace (in this embodiment, oxygen limitation is achieved by placing the biomass in a crucible, covering it with a lid, and pyrolyzing it under air conditions; of course, a protective atmosphere can also be used to directly perform pyrolysis under a protective atmosphere), the heating rate was 10°C·min-1, and the final temperature was maintained at 460°C for 1 hour. The obtained solid substance was named precursor carbon (3.3g of dry basis biomass was used for every 1g of precursor carbon).
[0048] Subsequently, the precursor carbon was mixed with FeSO4·7H2O in a mass ratio of 1:5, and mixed and impregnated at a water-solid ratio (mass ratio) of 20:1, stirred for 2 hours, and then left to stand overnight. The mixture was placed in a high-temperature furnace for high-temperature heat treatment. The specific steps were as follows: the sample was placed in a muffle furnace, and under oxygen-limited conditions (in this embodiment, the mixture was also placed in a crucible, and then covered with a lid for high-temperature heat treatment under air conditions; of course, a protective atmosphere can also be used, and high-temperature heat treatment can be directly performed under a protective atmosphere), heated to 700°C at a heating rate of 10°C·min-1, and kept at a constant temperature for 2 hours at this temperature. After cooling to room temperature, a biochar-ZVI material was obtained, which was recorded as a "biochar (700°C)-ZVI" sample. It needs to be stored in a sealed dryer before use to ensure its dryness and storage stability.
[0049] The precursor carbon was mixed with FeSO4·7H2O in the same dosage as mentioned above and then subjected to high-temperature heat treatment at 500°C and 900°C, respectively. The obtained samples were recorded as "biochar (500°C)-ZVI" sample and "biochar (900°C)-ZVI" sample, thus obtaining biochar-ZVI materials prepared at different temperatures.
[0050] In addition, XRD characterization was performed on the "biochar (500℃)-ZVI" sample, "biochar (700℃)-ZVI" sample and "biochar (900℃)-ZVI" sample. The results are as follows Figure 6As shown, it can be seen that both the "biochar (700℃)-ZVI" sample and the "biochar (900℃)-ZVI" sample have obvious characteristic peaks of zero-valent iron (ZVI); while the "biochar (500℃)-ZVI" sample did not observe the characteristic peak of zero-valent iron (ZVI), and the iron element was mainly loaded in the form of Fe3O4.
[0051] Example 2
[0052] Prepare to simulate the contamination of groundwater by chlorinated hydrocarbons. Specifically, place 500 mL of water containing carbon tetrachloride in a brown glass bottle, adjust the pH to 6.5, and the concentration of carbon tetrachloride to 50 ppm. Place the reaction bottle in a glove box to simulate the anaerobic environment of groundwater.
[0053] Then, 5 groups of control experiments were conducted, specifically:
[0054] a. Add 0.5 g of biochar-ZVI material (i.e., the "biochar (700°C)-ZVI" sample prepared in Example 1; the Fe mass ratio was measured to be about 25% by acid dissolution, and for ease of comparison, the Fe addition amount of 0.125 g was also followed in other groups in the subsequent test) to 500 mL of simulated chlorinated hydrocarbon-contaminated groundwater.
[0055] b. Add Fe to 500 mL of simulated chlorinated hydrocarbon contaminated groundwater 2+ (Specifically, in the form of adding FeSO4·7H2O compound) as a control; the corresponding FeSO4·7H2O dosage is 0.621g;
[0056] c. Add Fe3O4 to 500mL simulated chlorinated hydrocarbon contaminated groundwater as a control; the corresponding Fe3O4 dosage is 0.173g;
[0057] d. ZVI (ie, zero-valent iron, purchased from micron-sized iron powder) was added to 500 mL of simulated chlorinated hydrocarbon-contaminated groundwater as a control; the corresponding ZVI dosage was 0.125 g;
[0058] e. 500 mL of biochar was added to simulated chlorinated hydrocarbon contaminated groundwater as a control, wherein the biochar was obtained by pyrolyzing the precursor carbon prepared in Example 1 at a temperature of 700° C. and a nitrogen atmosphere for 2 h (the biochar did not contain iron-containing materials; after measurement, its specific surface area was 600 m 2 / g), the amount of biochar added was 0.5g;
[0059] Next, the reactors containing the five groups of samples were placed on a magnetic stirrer and stirred continuously at a speed of 600 r / min. Samples were taken at time points of 8, 24, 48, 72, 120, 168 and 336 h to analyze and determine the concentration of carbon tetrachloride.
[0060] like Figure 1 As shown, biochar (corresponding to group e), Fe 2+ (Corresponding to group b) has almost no reduction effect on carbon tetrachloride; using ZVI alone (corresponding to group d) has a carbon tetrachloride removal rate of 45.55% at 168h, and a carbon tetrachloride removal rate of 48.57% at 336h; using Fe3O4 system alone (corresponding to group c) has a carbon tetrachloride removal rate of 33.61% at 168h, and a carbon tetrachloride removal rate of 34.68% at 336h; using biochar-ZVI system (corresponding to group a) has a carbon tetrachloride removal rate of 95.99% at 168h, and a removal rate of 96.9% at 336h, with the best removal effect.
[0061] Example 3
[0062] This embodiment is substantially the same as Embodiment 2, except that the pH of the water body simulating chlorinated hydrocarbon-contaminated groundwater in Embodiment 2 is first adjusted to 3.0, and the material used is biochar-ZVI material (i.e., the "biochar (700°C)-ZVI" sample prepared in Embodiment 1).
[0063] like Figure 2 As shown, when the pH value of the polluted water body is 3.0, the removal rate of carbon tetrachloride is 83.62% at 168h and 92.1% at 336h, which also has a good removal effect.
[0064] Example 4
[0065] This embodiment is substantially the same as Embodiment 2, except that the pH of the water body simulating chlorinated hydrocarbon-contaminated groundwater in Embodiment 2 is first adjusted to 10.0, and the material used is biochar-ZVI material (i.e., the "biochar (700°C)-ZVI" sample prepared in Embodiment 1).
[0066] like Figure 2 As shown, when the pH value of the polluted water body is 10.0, the removal rate of carbon tetrachloride is 81.54% at 168h and 89.9% at 336h, which also has a good removal effect.
[0067] Example 5
[0068] This example is substantially the same as Example 2, except that the biochar-ZVI material prepared at 500° C. in Example 1 (ie, the “biochar (500° C.)-ZVI” sample) is used.
[0069] like Figure 4As shown, when the pH value of simulated chlorinated hydrocarbon contaminated groundwater was 6.5, the removal rate of carbon tetrachloride was 66.19% at 168h and 66.51% at 336h.
[0070] Example 6
[0071] This example is substantially the same as Example 2, except that the biochar-ZVI material prepared at 900° C. in Example 1 (ie, the “biochar (900° C.)-ZVI” sample) is used.
[0072] like Figure 4 As shown, when the pH value of simulated chlorinated hydrocarbon contaminated groundwater was 6.5, the removal rate of carbon tetrachloride was 97.99% at 168h and 98.9% at 336h.
[0073] Example 7
[0074] The conditions of this example are substantially the same as those of Example 2. This example explores the reduction efficiency of Fe(II), biochar, and biochar-Fe(II) on carbon tetrachloride, and conducts three groups of control experiments, specifically:
[0075] i.Fe(II) group: Fe is still used 2+ (i.e., still in the form of adding FeSO4·7H2O compound), the specific dosage and operation are consistent with those of group b in Example 2;
[0076] ii. Biochar group: The biochar used was still obtained by pyrolyzing the precursor carbon prepared in Example 1 at 700° C. in a nitrogen atmosphere for 2 h. The specific amount and operation were the same as those of Group e in Example 2;
[0077] iii. Biochar-Fe(II) system: using Fe(II) from group i simultaneously 2+ and the biochar in group ii, wherein the corresponding dosage of FeSO4·7H2O is 0.621 g; the usage of biochar is 0.5 g; specifically: the biochar and Fe(II) are fully reacted in 250 mL of deionized water for 1 hour, and then 250 mL of simulated chlorinated hydrocarbon (100 ppm) contaminated groundwater is added for reaction.
[0078] The reaction results of group i and group ii were the same as those of group b and group e in Example 2, i.e. Figure 1 As shown, Fe(II) and biochar alone had no significant removal effect on carbon tetrachloride; the reaction results of group iii are as follows Figure 5As shown in the figure, the removal efficiency of biochar-Fe(II) on carbon tetrachloride was 43.37% and 47.95% at 168h and 336h, respectively. The results showed that biochar and Fe(II) had a synergistic effect in removing carbon tetrachloride.
[0079] Example 8
[0080] This example explores the electron capacity of biochar, Fe(II) and biochar-Fe(II) systems. The amount of electrons that different systems can provide is determined by using a dielectric electrochemical method at a voltage of 0.61 V using an electrochemical workstation.
[0081] The samples in each group are as follows:
[0082] ①. Biochar group: The biochar used was still obtained by pyrolyzing the precursor carbon prepared in Example 1 at a temperature of 700°C and a nitrogen atmosphere for 2 hours; specifically, the biochar was prepared in an aqueous solution with a concentration of 4 g / L;
[0083] ②.Fe(II) group: Fe is still used 2+ (that is, still in the form of adding FeSO4·7H2O compound); specifically, Fe 2+ Aqueous solution with a concentration of 2 mM;
[0084] ③. Biochar-Fe(II) system: using biochar from group ① and Fe(II) from group ② simultaneously 2+ , the biochar was mixed with Fe(II) solution and reacted for 2 h to obtain the biochar solution, wherein the concentration of biochar in the mixed solution was 4 g / L, and the concentration of Fe(II) in the mixed solution was 4 g / L. 2+ The concentration in the mixed solution was 2 mM;
[0085] The results showed that the electron supply of biochar was 1.77mmol / L, the electron supply of Fe(II) was 1.82mmol / L, and the electron supply in the biochar-Fe(II) system was 5.51mol / L. The results showed that when biochar and Fe(II) coexisted, the electron supply increased by about 53.5% (i.e., (5.51-1.77-1.82) / (1.77+1.82)×100%=53.5%) compared to the simple addition of the electron supply in the individual systems. The two had a synergistic effect in terms of electron supply, that is, biochar and Fe(II) showed a synergistic effect in terms of electron supply.
[0086] Table 1 Comparison of the electron supply of biochar, Fe(II) and biochar-Fe(II)
[0087]
[0088] Example 9
[0089] This example discusses the content of Fe(II) after the reaction of biochar and Fe(III). The biochar used is still the biochar obtained by pyrolyzing the precursor carbon prepared in Example 1 at 700°C and nitrogen atmosphere for 2 hours; Fe(III) uses FeCl3·6H2O; specifically, 0.5g of biochar and 0.6g of FeCl3·6H2O are mixed and stirred evenly in 500mL of deionized water, and solid-liquid separation is performed after 8 hours. The obtained solid is cleaned with deionized water and XPS is performed to characterize and analyze the change in the valence state of Fe.
[0090] like Figure 3 As shown, the results show that 74.53% of the iron element in the solid obtained by the reaction is Fe(II), indicating that the biochar reacts with Fe(III) to obtain biochar-Fe(II).
[0091] Example 10
[0092] This example explores the effect of oxygen on the removal of chlorinated hydrocarbons after reacting with ZVI and biochar-ZVI.
[0093] For the ZVI system, 0.125 g of ZVI was added to 250 mL of deionized water and stirred for 1 day (under air conditions), the liquid was transferred to a glove box to maintain an oxygen-free atmosphere, and then 250 mL of 100 ppm carbon tetrachloride was added. The concentrations of ZVI and carbon tetrachloride and the pH were the same as those of group d in Example 2.
[0094] Biochar-ZVI system: 0.5 g of biochar-ZVI was added to 250 mL of deionized water and stirred for 1 day (under air conditions), the liquid was transferred to a glove box to maintain an oxygen-free atmosphere, and then 250 mL of 100 ppm carbon tetrachloride was added. The concentrations of biochar-ZVI and carbon tetrachloride and pH were consistent with those of group a in Example 2.
[0095] like Figure 7 As shown in the figure, after ZVI was stirred in the air, the removal efficiency of carbon tetrachloride decreased significantly, and the removal efficiency at 168h and 336h was 16.19% and 18.51% respectively; the removal efficiency of carbon tetrachloride in the biochar-ZVI system at 168h and 336h was 80.89% and 86.91% respectively, indicating that biochar-ZVI was less affected by oxygen.
[0096] The above embodiments are only examples. For example, in addition to bamboo, other woody wastes can also be used as biomass (of course, bamboo is more effective); for another example, the iron-containing material can also be other solid iron-containing materials, such as common iron salts, iron oxide powders, and zero-valent iron powders, as long as they are easy to disperse in water and can impregnate the biochar (the powder particle size can be, for example, micron level, or even finer). In addition, in addition to covering the lid and isolating oxygen, the oxygen-limited condition can also be constructed by using a protective atmosphere (such as nitrogen, argon, etc.). The method of the present invention also has a considerable removal effect on other chlorinated hydrocarbons such as trichloroethylene and chloroform.
[0097] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for treating groundwater contaminated by chlorinated hydrocarbons using biochar in combination with zero-valent iron, characterized in that: The following steps are involved: (1) mixing biomass with iron-containing materials and pyrolyzing them at 700-900° C. under oxygen-limited conditions to obtain a biochar-ZVI material; (2) The biochar-ZVI material is injected into the groundwater containing chlorinated hydrocarbons to be treated for a reaction for at least 7 days, thereby achieving the treatment of chlorinated hydrocarbons in the groundwater containing chlorinated hydrocarbons; wherein the pH value of the groundwater containing chlorinated hydrocarbons does not exceed 11.
2. The method according to claim 1, characterized in that: Step (1) specifically includes the following sub-steps: (1-1) preparing dried biomass with a particle size of ≤0.5 mm, and pyrolyzing the biomass at a temperature of 300° C. to 460° C. for 30 min to 2 h under oxygen-limited conditions to obtain precursor charcoal; (1-2) The precursor carbon and the iron-containing material are weighed and mixed in a mass ratio of (0.1-0.5):1, and then water is added to soak and stir and then allowed to stand; then the solid-liquid separation is performed, and the obtained solid is dried and pyrolyzed at a temperature of 700-900° C. under oxygen-limited conditions for 1-3 hours to obtain a biochar-ZVI material.
3. The method according to claim 2, characterized in that: In step (1-2), the amount of water added satisfies the water-to-solid mass ratio of (10-25):1; The stirring time is more than 2 hours, and the standing time is more than 12 hours.
4. The method according to claim 1, characterized in that: In step (2), the biochar-ZVI material is added to the groundwater containing chlorinated hydrocarbons to be treated at a concentration of 0.05-1.0 g / L.
5. The method according to claim 1, characterized in that: In step (2), the concentration of chlorinated hydrocarbons in the groundwater to be treated is between 20 and 1000 ppm.
6. The method according to claim 1, characterized in that: In step (1), the biomass is wood waste, preferably at least one of bamboo and coconut shell.
7. The method according to claim 1, characterized in that: In step (1), the mass ratio of the biomass dry basis to the iron-containing material is (0.3-2.0): 1; The iron-containing material is at least one of ferrous sulfate, ferric sulfate, ferrous chloride, ferric chloride, ferric oxide, zero-valent iron, and ferrosoferric oxide.
Citation Information
Patent Citations
A zero-valent iron bio-carbon source composite agent for in-situ remediation of chlorinated hydrocarbon-contaminated groundwater
CN107352657B
Method for degrading open-chain hydrochloric ether through tannic-acid-stable-nanoscale-zero-valent-iron-reinforced persulfate
CN109942071A
An in-situ remediation agent for groundwater contamination with chlorinated hydrocarbons, its preparation method and application
CN114477474B
A moldable in-situ remediation slow-release agent for chlorinated hydrocarbon pollutants and its preparation method
CN114479872B
Preparation method and application of double phosphorylated nano zero-valent iron with nanocracks
CN115475955B